Rapid deterioration of wetland in Bangladesh: a scenario of Noikandi Beel (Journal of Bio-Science, 2018)
Wetland aggregates at least a part of human heritage. It has direct impact on human culture and society. Besides, wetland comprises significant components in the context of local and national biodiversity. Beel wetland is a unique environment of floral and faunal association. In Bangladesh, wetland plays a vital role in its economic, industrial, ecological, socioeconomic and cultural attitudes. A study was conducted in the Noikandi beel where rapid destruction was observed due to anthropogenic activities. In the present study, seasonality and macro aquatic diversity and of the Noikandi beel Bangladesh was examined. Plant materials were collected from the beel once in a month for a period of 24 months. In the first 12 months, a total of 52 taxa have been recorded. Among them 40.38% was aquatic, 46.77% amphibians and 13.46% were found to be terrestrial. In addition, a rare taxon Euryale ferox Salisb was found. In the consecutive year of the study, 22.03% were aquatic, 52.54% terrestrial, 22.03% amphibians and1.69% was found to be macro algae. The rapid disappearance of aquatic plants is alarming. On the contrary, a good number of plants have been noted that is not associated with wetland environment indicating the transformation of wetland in to terrestrial ecosystem. Along with declining water depth and siltation other anthropogenic activities, agricultural, developmental initiatives have been identified as major threats, towards the Noikandi beel. The recommendations of the present study could be implemented by the government with the help of local people, as well as, this information may be useful for other beels of Bangladesh.J. bio-sci. 24: 33-43, 2016